Mondini Dysplasia Presenting as Otorrhea without Meningitis - Chien-Yu Lin; Hung-Ching Lin; Chun-Chih Peng; Kuo-Sheng Lee; Nan-Chang Chiu (Pediatrics and Neonatology)
Mondini dysplasia is a rare inner ear malformation that is usually only diagnosed after recurrent meningitis. Surgical intervention is mandatory. This report highlights the case of a patient with Mondini dysplasia who presented with hearing impairment and otorrhea and was diagnosed and treated before the occurrence of meningitis, thus preventing morbidity and neurologic sequelae. Hearing impairment may be the only manifestation of Mondini dysplasia, and the benefit of hearing screening is emphasized. Temporal bone computed tomography should be considered in children with unilateral sensorineural or mixed-type hearing impairment.